The role of C5a-C5aR1 axis in bone pathophysiology: A mini-review - Ruocco, Anna; Sirico, Anna; Novelli, Rubina; Iannelli, Silvia; Van Breda, Shane Vontelin; Kyburz, Diego; Hasler, Paul; Aramini, Andrea; Amendola, Pier Giorgio (Frontiers in Cell and Developmental Biology, 2022)
Bone remodeling is a physiological, dynamic process that mainly depends on the functions of two cell types: osteoblasts and osteoclasts. Emerging evidence suggests that complement system is crucially involved in the regulation of functions of these cells, especially during inflammatory states. In this context, complement component 5a (C5a), a powerful pro-inflammatory anaphylatoxin that binds the receptor C5aR1, is known to regulate osteoclast formation and osteoblast inflammatory responses, and has thus been proposed as potential therapeutic target for the treatment of inflammatory bone diseases. In this review, we will analyze the role of C5a-C5aR1 axis in bone physiology and pathophysiology, describing its involvement in the pathogenesis of some of the most frequent inflammatory bone diseases such as rheumatoid arthritis, and also in osteoporosis and bone cancer and metastasis. Moreover, we will examine C5aR1-based pharmacological approaches that are available and have been tested so far for the treatment of these conditions. Given the growing interest of the scientific community on osteoimmunology, and the scarcity of data regarding the role of C5a-C5aR1 axis in bone pathophysiology, we will highlight the importance of this axis in mediating the interactions between skeletal and immune systems and its potential use as a therapeutic target.